Health education of elderly women's breasts by circles of culture - Államy Danilo Moura e Silva; Izabel Cristina Falcão Juvenal Barbosa; Inez Sampaio Nery; Nayra Samanta Alves Luz; Ana Fátima Carvalho Fernandes (Universidad de Alicante, 2019)
Introduction: Health education as the health promotion strategy should be a social practice focused on the daily questioning, appreciation of life experiences, adapted to different realities. Objective: The study has the general objective to describe the development of educational activities for prevention and early detection of breast cancer in older women through crop circles. Methods: This is an exploratory descriptive research with a qualitative approach. Subjects were 13 elderly women enrolled in a Basic Health Unit in the city of Floriano, Piauí, Brazil. The theoretical foundation of culture circles created by Paulo Freire, and the lines evaluated by Bardin content analysis. Results: The crop circles were a dialogue enhancement of the environment in which the words were generated consonant with the experiences and living habits of the participants, encouraging interaction. Speaking at breast cancer, the words expressed were related to fear and despair, confirming the association of this neoplasm with feelings of intense sadness. Conclusion: We conclude that the implementation of crop circles led to the participant group, the reflectivity of their conduct to position themselves as protagonists of their history of health/illness related to what was put to discussion, facilitating the achievement of a better quality of life.